Hepatitis E Virus: First Description in a Pet House Rabbit. A New Transmission Route for Human?. Issue 3 (12th March 2015) - Caruso, C.; Modesto, P.; Prato, R.; Scaglione, F. E.; De Marco, L.; Bollo, E.; Acutis, P. L.; Masoero, L.; Peletto, S.
Summary: In this work, we identified for the first time hepatitis E virus (HEV) in a pet house rabbit, an adult 7 years old female of domestic rabbit ( Oryctolagus cuniculus ). Importantly, the resulting phylogenetic tree showed that the HEV strain identified in the pet house rabbit was closely related to a human HEV sequence; this finding reawakens concerns regarding the zoonotic risk represented by HEV in animals and expands to house rabbit the spectrum of potential source of infection for humans. Potential for domestic transmission of HEV to humans should be taken into account.